GENETIC ANALYSIS AND TRAITS ASSOCIATION IN RICE (Oryza sativa L.) UNDER SALT-STRESS CONDITIONS - P. RAGHUVEER RAO; K. SUMALINI, P. HIMA BINDU, G. SHIVA PRASAD, CH. DAMODAR RAJU, RAMAN MEENAKSHI SUNDARAM (The Journal of Research, PJTSAU, 2023)
Salinity stress is one of the main problems for the rice crop, as it reduces the production and productivity of the grain yield signifcantly. Genetic variability studies provide basic information concerning the genetic properties of the population based on which breeding methods could be formulated for further improvement of the crop. The estimates of heritability, coefficients of variability and genetic advance was computed in F1s of 24 crosses for 10 characters including yield, yield contributing traits and salt-tolerane under salinity condition during Kharif 2021. A joint consideration of PCV, GCV, heritability broad sense and genetic advance as percentage revealed that spikelet sterility percentage (62.01, 52.35, 71.3 and 18.14%), number of unfilled grains per panicle (50.42, 39.23, 60.5 and 25.54%) and total number of grains per panicle (26.75, 25.25, 89.1 and 109.76%) combined high PCV, GCV, high broad sense heritability and high genetic advance. High heritability coupled with high and moderate genetic advance was observed for all the plant traits under study except for days to 50% flowering and panicle length. Correlation studies revealed that seed yield per plant was positively and significantly correlated with number of productive tillers per plant and total number of filled grains per panicle. However seed yield plant per plant was negatively significantly associated with sterility percentage.